EFEKTIVITAS PERUMDA AGRO SUKABUMI MANDIRI DALAM UPAYA PEMBANGUNAN DI KABUPATEN SUKABUMI - Fitria, Anna Fitria Agustina (STISIP Widyapuri Mandiri Sukabumi, 2025)
This research is motivated by the existence of a problem found during the pre-survey, namely the lack of publications regarding Perumda ASM so that there are still people who do not understand about Perumda ASM, lack of public knowledge about the function of Perumda ASM in increasing the development of Sukabumi Regency, the extent of Sukabumi Regency land that has the potential to its natural resources cannot be managed, making Perumda ASM unable to work on it as a whole. The role of Perumda ASM in increasing development in Sukabumi Regency has not been effective because it has just been established, so there is no conformity in the amount of income, the timeliness of income is not appropriate because Perumda ASM has just started operating, and the quality of resources management human resources are not optimal. These problems can be seen from the theory used, namely Hidayat's theory with 3 research dimensions, namely quality, quantity, and time. Effectiveness is a measurement of success in achieving the goals that have been set. So the purpose of this research is to find out how far the Effectiveness of Perumda Agro Sukabumi Mandiri has been achieved in Development Efforts in Sukabumi Regency. The approach used by researchers is qualitative with descriptive methods, data collection techniques using interview techniques, observation, and documentation and applying triangulation techniques. Then data analysis using data reduction, data presentation, and drawing conclusions. The informants in this study amounted to 6 people, using purposive sampling and snowball sampling techniques. The informants were the Main Director of Perumda Agro Sukabumi Mandiri, Head of General Affairs and Personnel Division, Head of Planning and Evaluation Division, Planning and Evaluation Staff, Agribusiness Actors, and the Community. The results of the study show that the effectiveness of Perumda Agro Sukabumi Mandiri in development efforts in Sukabumi Regency has not gone well. This can be seen from the quality of the potential and the community's understanding of the role of Perumda ASM which is not yet good, the quantity of targets for achievement and the suitability of the amount of income is not appropriate, the timeliness of income and reporting is not correct. The conclusion of this study is that because the indicators of each are not appropriate, the effectiveness of Perumda Agro Sukabumi Mandiri in development efforts in Sukabumi district has not been achieved.